Assessing the potential of trade along the proposed Shymkent Tashkent Khujand economic corridor. (Metro Manila, Philippines Asian Development Bank, 2020)
The assessment explores the transit of international goods in cities and oblasts (administrative divisions or regions) in STKEC and and trade regimes in the three countries. The report also identifies and analyzes existing barriers and opportunities for trade expansion. It provides recommendations for various stakeholders on policy measures for improvement under the framework of the STKEC development.
Keywords: India Economic integration; Industry and state; Electronic books